An Iteration to a Common Point of Solution of Variational Inequality and Fixed Point-Problems in Banach Spaces - H. Zegeye; N. Shahzad (Journal of Applied Mathematics)
We introduce an iterative process which converges strongly to a common point of solution of variational inequality problem for a monotone mapping and fixed point of uniformly Lipschitzian relatively asymptotically nonexpansive mapping in Banach spaces. As a consequence, we provide a scheme that converges strongly to a common zero of finite family of monotone mappings under suitable conditions. Our theorems improve and unify most of the results that have been proved for this important class of nonlinear operators.